TRIPS flexibilities and access to medicines: An evaluation of barriers to employing compulsory licenses for patented pharmaceuticals at the WTO - Anna S. Y. Wong; Clarke B. Cole; Jillian Clare Kohler (South Centre, 2022)
Under Articles 31 and 31bis of the TRIPS Agreement, WTO members may validly sanction the use of a patented invention without the patent owner's authorization by issuing a compulsory license (CL). In the pharmaceuticals space, governments have historically employed compulsory licenses to compel originator manufacturers to license their patents to generic manufacturers before patent expiry, increasing the supply and reducing the price of patented pharmaceuticals domestically. This paper evaluates the three primary barriers to employing compulsory licenses for pharmaceuticals underscored by members during TRIPS waiver discussions at the WTO: (1) a lack of enabling domestic legislation, (2) a lack of domestic manufacturing capacity coupled with an unworkable Article 31bis importation system, and (3) consistent political pressure from other members to refrain from issuing compulsory licenses. A survey of members' domestic compulsory license legislation finds that virtually all members have enacted enabling legislation under Article 31 for the issuance of compulsory licenses to supply their local markets. However, implementation of Article 31bis is limited by a lack of enabling compulsory license export legislation, streamlined administrative processes, or both across all members, preventing members lacking domestic manufacturing capacity from importing pharmaceuticals. An analysis of USTR Special 301 Reports from 1994-2021 further reveals that countries have consistently been placed on the Special 301 Report Priority Watch List for issuing pharmaceutical compulsory licenses, with instances as recent as 2020. As such, general reluctance by members to issue compulsory licenses due to overt political pressure through the Special 301 Report is likely warranted. These results highlight a range of barriers preventing the full use of compulsory licenses for pharmaceuticals under the current Article 31 and 31bis framework, with the effects disproportionately borne by member states lacking domestic manufacturing capacity.
Keywords: 300; Access to Medicines; Article 31 TRIPS; Article 31bis; Compulsory Licenses; COVID-19; Flexibilities; Generic Medicines; Intellectual Property; Pandemic; Patent; Pharmaceuticals; Public Health; TRIPS; TRIPS Agreement; TRIPS Flexibilities; TRIPS Waiver; US Special Section 301; World Trade Organization (WTO)